A Framework for Sustainable Non-Profit Crowdsourcing Applications - Aris H.; Mahmud F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Profitability; Application developers; Monetary rewards; Non-profit; Crowdsourcing